2023
DOI: 10.1038/s41598-023-29512-0
|View full text |Cite
|
Sign up to set email alerts
|

Political ideology and moral dilemmas in public good provision

Abstract: Individuals often face dilemmas in which non-cooperation serves their self-interest and cooperation favors society at large. Cooperation is often considered the moral choice because it creates equality and fairness among citizens. Accordingly, individuals whose political ideology attaches greater value to equality than to agency and self-reliance should not only cooperate on more rather than less efficient public goods, but also more on public goods from which individuals benefit equally rather than unequally.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Taking our investigation a step further, we examined individual variations in behavior and uncovered distinct moral principles held by people, recognizing that people may espouse diverse beliefs about moral decision-making [17,18]. The rst cluster, comprising the majority of participants, displayed both rankreversal aversion and inequality aversion.…”
Section: Discussionmentioning
confidence: 99%
“…Taking our investigation a step further, we examined individual variations in behavior and uncovered distinct moral principles held by people, recognizing that people may espouse diverse beliefs about moral decision-making [17,18]. The rst cluster, comprising the majority of participants, displayed both rankreversal aversion and inequality aversion.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, cooperation leads to optimal benefits for the supply chain system [51]. The cooperation selection mode of the general contractor and subcontractor is not related to the degree of contribution, and the general contractor prefers the egoistic decision mode, while the subcontractor prefers the centralist decision mode.…”
Section: Discussionmentioning
confidence: 99%
“…In Part 1, participants completed several personality measures, including the social value orientation (SVO) slider (Murphy et al, 2011) capturing SVO and inequality aversion. The other personality measures served research questions outside the scope of the present manuscript and are reported in Hoenig et al (2023) (see https://aspredicted.org/IIV_LVO). The very few and minor deviations from the preregistration are detailed in the online supplemental materials.…”
Section: Methodsmentioning
confidence: 99%